Molecular-crowding effects on single-molecule RNA folding/unfolding thermodynamics and kinetics - Dupuis, Nicholas F.; Holmstrom, Erik D.; Nesbitt, David J. (Proceedings of the National Academy of Sciences - PNAS, 2014)
The effects of “molecular crowding” on elementary biochemical processes due to high solute concentrations are poorly understood and yet clearly essential to the folding of nucleic acids and proteins into correct, native structures. The present work presents, to our knowledge, first results on the single-molecule kinetics of solute molecular crowding, specifically focusing on GAAA tetraloop–receptor folding to isolate a single RNA tertiary interaction using time-correlated single-photon counting and confocal single-molecule FRET microscopy. The impact of crowding by high–molecular-weight polyethylene glycol on the RNA folding thermodynamics is dramatic, with up to ΔΔ G ° ∼ −2.5 kcal/mol changes in free energy and thus >60-fold increase in the folding equilibrium constant (K ₑq) for excluded volume fractions of 15%. Most importantly, time-correlated single-molecule methods permit crowding effects on the kinetics of RNA folding/unfolding to be explored for the first time (to our knowledge), which reveal that this large jump in K ₑq is dominated by a 35-fold increase in tetraloop–receptor folding rate, with only a modest decrease in the corresponding unfolding rate. This is further explored with temperature-dependent single-molecule RNA folding measurements, which identify that crowding effects are dominated by entropic rather than enthalpic contributions to the overall free energy change. Finally, a simple “hard-sphere” treatment of the solute excluded volume is invoked to model the observed kinetic trends, and which predict ΔΔ G ° ∼ −5 kcal/mol free-energy stabilization at excluded volume fractions of 30%.